"I was Born to do This": Faculty Experiences Teaching Graduate-Level Diversity Courses. (April 2023) - Morgan, Melissa L.; Marin, Patricia
Background: Little research has focused on teaching graduate-level diversity courses, particularly from the faculty standpoint. Such pedagogy calls for unique skills and contains many challenges. Objective: The purpose of the study was to better understand what works and what is needed to support instructors of graduate-level diversity courses, as well as common challenges that these instructors face. Method: Using Charmaz' Constructivist Grounded Theory approach, data from 20 qualitative interviews were analyzed for emergent themes. Results: Four over-arching themes emerged: (a) Challenges in Teaching the Course, (b) Impact on the Instructor, (c) Coping with Course Challenges, and (d) Feelings about Teaching Multicultural Courses . Conclusion: Findings suggest the unique nature of graduate-level diversity courses, and the need for resources and support for instructors of such courses. Teaching Implications: Teaching diversity courses can take a personal and professional toll on the instructor. University systems should be aware of this and support structures and resources for such teaching.